Avaliação do consumo alimentar de lactentes com fenilcetonúria em uso de aleitamento materno - Jacqueline Siqueira Santos (2007)
Breast-feeding in phenylketonuria (PKU) is a established technique and now is spreading in some countries. But there are few researches about the real intake of nutrients when it is used. The aim of study was to evaluate nutrient intakes (phenylalanine, protein, tyrosine and calories) of newborns and infants breast-feeding in phenylketonuria (PKU). This is a retrospective study using the database of children with PKU followed at Newborn Screening Program of Minas Gerais. Measurements (weight, height, head circumference) and 24-hour dietary recalls were collected. Agroup of 39 infants, aged from 0 to 6 months using breast-feeding were compared with a controlgroup of 39 infants with PKU using formula milk as a source of phenylalanine. Groups were paired by sex and time of using breast-feeding or formula milk, until a maximum of 6 months.Anthropometric evaluations were made using software EPI INFO 6.0 and statistical analyses of nutrient intakes were made using software LogXact 4.0. The mean consumption nutrient throughout the study for the breast-feeding and control groups were respectively 128,54±20,45Kcal/Kg/day and 164,6±66,70 Kcal/Kg/day; 44,37±17,68 mg/Kg/day and 46,72±15,60 mg/Kg/day of phe; 3,09±0,40 g/Kg/day and 2,85±0,43 g/Kg/day of protein and 180,34±28,50 mg/Kg/day and 128,54±20,45 mg/Kg/day of tyr. There was a statistically significant difference inprotein and caloric intake. Breast-fed group presented 5 times more chances to show adequate values of protein intake than control-group does, and the chances for breast-fed patients to have adequate levels of caloric consumption are 10 times those for control-group. Anthropometricevaluation demonstrated that most of the children, of both groups, presented z-scores within limits of normality (Z > -2), with favorable evolution of evaluated indexes (Weight/Age, Height/Age, Weight/Height and head circumference). Breast-feeding in PKU children, afforded adequate intake of phenylalanine, protein, tyrosine and calories and, when compared with formula fed presented advantages in protein and caloric intake. Both groups presented normal growth.